MISFIRES OF CROSS-CULTURAL LEGAL COMMUNICATION IN THE PERSPECTIVE OF J. AUSTIN AND J. LANGSHAW AUSTIN - KOROLEV, Sergey (Comparative Legilinguistics, 2010)
The article is meant to serve both theory and practice in the cross-roads area where legal theory meets linguistic philosophy. The legal perspective is represented by the famous command theory of John Austin, who is often regarded as the founding father of anglo-american branch of legal positivism. The linguistic perspective is represented by the speech acts theory elaborated by John Langshaw Austin. It is argued that the command theory is only of marginal use for any process of crosscultural legal communication. The reason behind this argument is that the command theory is grossly reductionist in its nature (―colonel – lieutenant‖) and cannot therefore embrace a trilateral reality of cross-cultural legal communication (speech originator – interpreter – audience). But the imperative theory may be useful if applied to ―misfires‖ of the whole process of legal oral translation. By transforming the said trilateral reality to any dichotomy in the sense of the command theory, i.e. by bracketing together any two of the said agents and by insulating the third one- we inevitably arrive at some sort of ―misfire‖ or even collapse of the whole procedure. Further the common view is challenged that the only source of such ―misfires‖ lies in poor quality of interpretation. It is argued that both the speech originator and even somehow inadequate audience may share the final failure. The eventual outcome of the article may be described as an attempted synthesis of the speech acts theory of John Langshaw Austin and sociology of law as elaborated by German professor Werner Krawietz. The interdisciplinary approach to discussed ―misfires‖ of cross-cultural legal communication resulted in formulating a series of bilateral rules, which are obligatory both for the speech originator and the interpreter if the most unacceptable ―misfires‖ of legal oraltranslation are to be avoided.